Forage quality and beef cow preference is affected by wrap type of conventional and reduced-lignin alfalfa round bales stored outdoors. Issue 3 (9th September 2020) - Reiter, Amanda S; DiCostanzo, Alfredo; Webb, Megan; Zeltwanger, Josh; Sheaffer, Craig C; Jaqueth, Aubrey; Martinson, Krishona L
Abstract: Storing hay outdoors can result in detrimental changes in forage quality. Additionally, alfalfa ( Medicago sativa L.) cultivar may influence dry matter intake (DMI) and hay waste when feeding livestock. The objectives were to determine the effects of conventional or reduced-lignin alfalfa round bales stored outdoors and wrapped with plastic twine, net wrap, or B-Wrap on forage quality, beef cow preference, and hay waste. Round bales made from reduced-lignin ( n = 12) or conventional ( n = 12) alfalfa cultivars were baled and stored outdoors for 16 mo. Within each cultivar, four bale replicates were bound with plastic twine, net wrap, or B-Wrap. After storage, bales were fed in a switchback design with period confounded with alfalfa cultivar to 18 lactating Angus cows ( Bos Taurus L.). The pairs had ad libitum access to three round-bale feeders where bales of each wrap type were placed for eight 48 h periods. Position of round bale wrap type was rotated according to a Latin Square arrangement. Bales were weighed and waste surrounding each feeder was collected at 24 and 48 h to calculate DMI and hay waste. Statistical significance was set at P < 0.05. Alfalfa cultivar did not impact any of the response variables ( P > 0.05). At feeding, round bales wrapped in net wrap had greater ( P < 0.015) moisture content (16.4%) compared with those wrapped with B-Wrap (12.8%). Neutral detergent fiber was lower ( P = 0.03) in bales wrapped in B-Wrap (46%) compared with twine-tied bales (49%) while net wrapped bales were not different. Total digestible nutrients ( P = 0.02), and relative feed value ( P = 0.04) were lower in twine-tied bales compared with B-Wrap while net wrapped bales were not different. Twine (7.1 × 10 6 colony forming units [CFU]/g) and net wrap (4.7 × 10 6 CFU/g) bales had greater ( P < 0.0001) mold counts than B-Wrap bales (4.8 × 10 4 CFU/g), while concentrations of other forage components and yeast counts were not different among wrap types ( P > 0.05). Total DMI, and DMI during the first 24 h, were greater ( P ≤ 0.032) for B-Wrap bales compared to twine-tied bales indicating preference for hay wrapped in B-Wrap; net wrapped bales were not different. Dry matter intake in the first 24 h was negatively associated with the mold count ( r = −0.52; P = 0.02), and hay waste was not affected by wrap type ( P > 0.05). These results confirm that wrap type affected forage quality and mold counts, which in turn influenced beef cattle preference of round bales stored outdoors.